Russian Manes for Liver. Word-Building and Semantic Reconstruction - Ушинскене, В. (Kalbotyra, 1997)
A group of anatomical terms denoting liver in Russian and its dialects is being analysed in the paper. As the analysis shows this group of terms was formed at the epoch of dialectical development of Proto-Slavonic and at the time of independent formation of Slavonic languages.The most archaic Russian names for liver continue Proto-Slavonic stems *o̧tro-/*ętro and *къseпь. The main anatomical term of modern Russian *pečenь is to be regarded as a semantic innovation of eastern and western Slavonic languages. Russian-Polish isogloss is represented by the word *osьгdьje.The Russian terms proper such as жельцо, золоза, кровеник and other are of secondary semantic. The established semantic patterns are being presented.